Gram-Negative Bacterial Lipopolysaccharide Stimulates Activin A Secretion from Human Amniotic Epithelial Cells - Yumiko Abe; Risa Marukawa; Nami Tsuru; Maki Sato; Hiroko Matsuda; Hisanobu Sadakata; Takashi Kameda; Takashi Minegishi (International Journal of Endocrinology)
Activin A is involved in inflammation. The present study was performed to clarify if lipopolysaccharide, a component of Gram-negative bacteria, stimulates activin A secretion from human amniotic epithelial cells and to determine if activin A plays a role in amnionitis. Fetal membranes were obtained during elective cesarean sections performed in full-term pregnancies of patients without systemic disease, signs of premature delivery, or fetal complications. Amniotic epithelial cells were isolated by trypsinization. The activin A concentrations in the culture media were measured by enzyme-linked immunosorbent assay, and cell proliferation was assessed by 5-bromo-2′-deoxyuridine incorporation. Amniotic epithelial cells secreted activin A in a cell density-dependent manner, and lipopolysaccharide (10 μg/mL) enhanced the secretion at each cell density. Lipopolysaccharide (10–50 μg/mL) also stimulated activin A secretion in a dose-dependent manner. Contrary to the effect of activin A secretion, lipopolysaccharide inhibited cell proliferation in amniotic epithelial cells. The present study suggests that lipopolysaccharide stimulation of activin A secretion may be a mechanism in the pathogenesis of amnionitis.